Effectiveness of Bridge Programme at the Elementary Stage - Yadav, Neetu; Singh, Satpal (THE PRIMARY TEACHER, 2017)
A bridge programme was conducted in 84 schools of Delhi. An experimental study was carried out examine the effectiveness of the programme on pupil achievement in Hindi and mathematics in Classes VI, VII and VIII. A total of 1,445 students were surveyed. Three separate questionnaires for parents, teachers and principals were administered to know their perception about the utility of the bridge programme. Pre– and post–tests were conducted, and ‘t–value’ was calculated to find out the significant difference on the academic achievement of the students. The findings reveal significant difference between the pre– and post–test scores. The results indicate a significant increase in the achievement levels of the students in both the subjects. Hence, the pedagogical interventions were found to be highly significant, in terms of contributing to pupil achievement, in both the subjects.